ANALISA PERFORMANSI ENGINE SOHC PADA MOBIL DAIHATSU TARUNA TIPE CSX - W Naibaho; S Sitompul; J S Purba (Cered Indonesia Institute, 2021)
To determine the characteristics and capabilities of the machine, a series of tests were carried out using the SOHC system. In this test, several parameters can be shown, namely; torque, effective shaft power, average pressure, specific fuel consumption.The research was carried out at engine shaft rotation of 1200 rpm to 4000 rpm with 6000 rpm as a benchmark for loading on gasoline engine performance measurements were made on fuel consumption, load, rotation and flow rate of each with a measuring instrument, while the testing equipment used was a gasoline motor. Daihatsu Taruna 1500 cc. Torque as a function of rotation of the Daihatsu Taruna Type CSX engine has a higher torque. The engine output power as a function of the shaft rotation The Daihatsu Taruna Type CSX engine has a larger shaft power. The engine provides driving performance at high rpm and is also fuel efficient. Effective engine power as a shaft rotation The Daihatsu Taruna Type CSX engine has an effective engine power. The average effective pressure between the Daihatsu Taruna Type CSX engine and the EFI (Electronic Fuel Injection) fuel supply system. These results indicate that the Daihatsu Taruna engine is more powerful at high engine speed with maximum torque and remains efficient in fuel consumption.